Inequality of Public Transportation Policy in the Disruptive Era Between Online and Conventional Transportation - Tuti, Retnowati Wahyuning Dyas; Setiawan, Asep; Zebua, Winda Dwi Astuti; Rudiatin, Endang; Izzatusholekha, Izzatusholekha; Handayani, Nida; Andiani, Devia (Universitas Muhammadiyah Yogyakarta, 2022)
Indonesia is one of the countries with a large market for online transportation. This paper describes a meta-analysis on policy inequality regarding public transportation. Meta-analysis and Computer Assisted Qualitative Data Software (CAQDAS) were utilized to evaluate the inequality of public transportation policy for conventional transportation. Scopus search engine was also used to identify broad literature on a particular policy regulation in Indonesia between 2010 and 2021. Then, this study employed online news related to the conflict between conventional and online transportation. The result disclosed a policy inequality between online and conventional transportation based on the social movement on online media. Thus, the government has to implement a strict policy applicable to transportation. The words “protest”, “regulation,” and “police” were also seen clearly on the issue. In addition, the protesters, comprised of drivers from Uber, Grabcar, and Go-Car, said that Transportation Ministry Regulation No 32/2016 would disadvantage them because it is too difficult to comply with the requirements. Hence, the government can decide on self-regulation to design a policy for online transportation. In this case, state law is still necessary when monopolistic attempts are made, unfair competition exists, public safety as consumers is maintained, and taxes are collected.